2005
DOI: 10.1093/molehr/gah139
|View full text |Cite
|
Sign up to set email alerts
|

The NGFI-B family of transcription factors regulates expression of 3β-hydroxysteroid dehydrogenase type 2 in the human ovary

Abstract: The nerve growth factor-induced clone B (NGFI-B) family of transcription factors are orphan members of the steroid hormone receptor superfamily. The NGFI-B expression was recently shown in the rat ovarian tissue and appears to be regulated by gonadotrophins. The purpose of our study was to investigate the role of the three members of this family [NGFI-B, Nur-related factor 1 (NURR1) and neuron derived orphan receptor 1 (NOR-1)] in the transcription of genes that encode key steroidogenic enzymes and examine exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…6, A and B), both of which regulate CYP21A2 transcription (17,50). Nur77 also modulates StAR gene expression (18). Further, the expression of the transcription factor DAX-1 is significantly down-regulated in ASAH1 KD cells (Fig.…”
mentioning
confidence: 84%
“…6, A and B), both of which regulate CYP21A2 transcription (17,50). Nur77 also modulates StAR gene expression (18). Further, the expression of the transcription factor DAX-1 is significantly down-regulated in ASAH1 KD cells (Fig.…”
mentioning
confidence: 84%
“…NR4A1 binds DNA as a monomer to the sequence AAAAGGTCA, called NR4A1 response element (NBRE), that is very similar to that recognized by the nuclear receptor steroidogenic factor 1 (NR5A1, SF1; Wilson et al 1993), an essential regulator of expression of many steroidogenic genes (reviewed in Parker et al 2002, Val et al 2003. In Leydig cells, NR4A1 has been found to regulate genes involved in steroidogenesis (Zhang & Mellon 1997, Bassett et al 2004, Havelock et al 2005, Martin & Tremblay 2005, including Star (Martin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NR4A1 g.3952A>G may have lower linkage disequilibrium with the causative mutation in this Large White population. The NR4A1 gene is a nuclear steroid hormone receptor and is expressed in the ovarian follicle and ovary (Park et al, 2001) and plays an important role in the regulation of steroid signaling and follicle maturation (Havelock et al, 2005;Li et al, 2010;Dai et al, 2012). It has been reported that increased expression of NR4A1 in pigs under selection for enhanced ovulation rate and embryonic survival may be correlated with an increased sensitivity to steroid hormones in ovarian follicles .…”
Section: Discussionmentioning
confidence: 99%
“…The gene is rapidly and transiently induced by a luteinizing hormone surge in granulosa cells of preovulatory follicles in rats (Park et al, 2001) and humans (Havelock et al, 2005). The porcine NR4A1 gene is highly expressed in the ovary and uterus (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%